Globalisation, Urbanisation, and the Common Good - Hogan, Linda (Concilium, 2019)
Globalisation has changed the nature of contemporary economic and political life and has created new ethical challenges. In this context the exponential growth of cities and the trajectory of urbanisation not only creates new social, political and economic challenges, but it also magnifies the difficulties associated with creating just, inclusive and equitable political and economic structures. The fact of urbanisation raises, in an acute way, the question of how to live well in the midst of intense diversity. Thus, the question of how cities can contribute to managing pluralism, while also promoting social cohesion, is a crucial one for contemporary society. Building a life in common is a vital task, and must be grounded in the integrity of cultures, traditions and life-worlds.